Femoral Vessel Occlusion Enhances Cardiac and Cerebral Perfusion in a Porcine Model of Cardiac Arrest - Joshua Y. Kim; Benjamin Usry; Maren L. Downing; Samuel W. Seigler; Heather Holman; Jennie H. Kwon; Kristi Helke; Rupak Mukherjee; Jeffrey A. Jones; Kristen M. Quinn (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Closed chest compressions during cardiopulmonary resuscitation (CPR) mechanically circulate blood to the organs during cardiac arrest, yet cardiac arrest remains among the most fatal diseases, with a mortality rate that exceeds 85% to 90% globally. Novel methodologies to improve organ perfusion, particularly in resource‐restricted settings, are overdue. This study evaluated the efficacy of external femoral vessel occlusion (FVO) during CPR in a large mammal model. Methods Thirteen adult Yorkshire pigs were instrumented with vascular and electrophysiologic monitoring lines. Hemodynamic measures and cardiac and cerebral perfusion in the pre‐ and postarrest conditions were quantified via fluorescent microspheres infused into the circulation. Control (n=7) animals underwent routine CPR, whereas experimental (n=6) animals received CPR and FVO via external compression to the femoral vessels during the entirety of the 30‐minute resuscitative phase. The primary outcome was mean arterial pressure, and secondary outcomes included cerebral and cardiac perfusion. Results During native heart function, external FVO demonstrated a significant increase in mean arterial pressure (73±3 versus 62±2 mm Hg, P<0.001). During cardiac arrest, animals undergoing CPR with FVO had a significantly higher mean arterial pressure compared with CPR alone (49±9 versus 32±3 mm Hg, P<0.001). CPR with FVO significantly increased cardiac (181 versus 80 mean fluorescence intensity, P=0.014) and cerebral perfusion (119 versus 27 mean fluorescence intensity, P<0.001). Conclusions CPR with FVO significantly increased mean arterial pressure, cardiac perfusion, and cerebral perfusion over CPR alone. These findings suggest FVO may represent a novel adjunctive strategy and therapeutic opportunity to enhance cerebral and cardiac perfusion, thereby decreasing cardiac arrest morbidity and mortality.